2021
DOI: 10.3390/ijms221910683
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Open Reading Frame Mediated Translation of WNK8 Is Required for ABA Response in Arabidopsis

Abstract: With no lysine (K) (WNK) kinases comprise a family of serine/threonine kinases belonging to an evolutionary branch of the eukaryotic kinome. These special kinases contain a unique active site and are found in a wide range of eukaryotes. The model plant Arabidopsis has been reported to have 11 WNK members, of which WNK8 functions as a negative regulator of abscisic acid (ABA) signaling. Here, we found that the expression of WNK8 is post-transcriptionally regulated through an upstream open reading frame (uORF) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…The uORFs are essential regulatory elements located in the 5’ UTR of main open reading frames (mORFs). Recent bioinformatics analyses estimate that approximately 35% of total plant transcripts contain uORFs ( Silva et al., 2019 ; Li et al., 2021 ). These uORFs are known to act as inhibitors, repressing the initiation of mORF translation via ribosome stalling ( Silva et al., 2019 ; Zhang et al., 2020 ).…”
Section: Upr Pathways In Plant Cells: Mechanisms and Regulationmentioning
confidence: 99%
“…The uORFs are essential regulatory elements located in the 5’ UTR of main open reading frames (mORFs). Recent bioinformatics analyses estimate that approximately 35% of total plant transcripts contain uORFs ( Silva et al., 2019 ; Li et al., 2021 ). These uORFs are known to act as inhibitors, repressing the initiation of mORF translation via ribosome stalling ( Silva et al., 2019 ; Zhang et al., 2020 ).…”
Section: Upr Pathways In Plant Cells: Mechanisms and Regulationmentioning
confidence: 99%
“…These works cover outstanding advances in the molecular mechanisms by which GA and ABA control different aspects of plant physiology, development and for ABA, also in the response to abiotic stresses. In line with this, the original research articles investigate the effects of ABA on epicuticular wax metabolism regulation in a citrus fruit cultivar [ 9 ], the regulation of WNK kinases and their comprehensive interaction with ABA components [ 10 ], CCD family members in poplar and their expression patterns in response to ABA and abiotic stress [ 11 ], the molecular function of NAC transcription factor PwNAC11 in drought stress [ 12 ], the interaction between AFPs and DELLA proteins [ 13 ], and the molecular mechanism by which AGB1 regulates the GA pathway in Arabidopsis [ 14 ]. The reviews published in this Special Issue focus on how ABA regulates plant development and stress tolerance through alternative splicing [ 15 ], the mechanisms of ABA-mediated drought stress responses in plants [ 16 ], the roles of ABA and GA in stem/root tuber development [ 17 ] and the molecular mechanisms underlying ABA and GA regulation of seed development from embryogenesis to maturation [ 18 ].…”
mentioning
confidence: 99%
“…Interestingly, the presence of a conserved peptide encoded by an upstream open reading frame (uORF) called CPuORF58 has been reported in the 5′-UTR of WNK8 [ 20 ]. Li et al [ 10 ] thoroughly studied WNK8 regulation and interaction with ABA components. They indicated that WNK8 negatively regulates ABA response during seed germination and post-germination development.…”
mentioning
confidence: 99%
See 1 more Smart Citation